The Rising Influence of Family Background on Early School Performance - Simen Markussen; Knut Røed (Institute of Labor Economics (IZA), 2023)
We use administrative data from Norway to examine recent trends in the association between parents' prime age earnings rank and offspring's educational performance rank by age 15/16. We show that the intergenerational correlation between these two ranks has increased over the past decades, and that offspring from economically disadvantaged families have fallen behind. This has happened despite public policies contributing to leveling the playing field. In particular, we show that the expansion of universal childcare and, more recently, the increased teacher-pupil ratio in compulsory school, have disproportionally benefited lower class offspring. The rising influence of parents' earnings rank can partly be explained by a strengthened intragenerational association between earnings rank and education among parents, as educational achievement has an inheritable component. Yet a considerable unexplained rise in the influence of family background remains, pointing towards an impending decline in intergenerational economic mobility.
Keywords: I24; J62; 330; Intergenerational mobility; achievement gaps; parental influence; meritocracy; GPA